2011
DOI: 10.2753/eee0012-8775490301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ownership and Management Changes on Productivity in Privatized Montenegrin Firms

Abstract: This study reflects the relationship between ownership change, ownership concentration, management turnover, and productivity of Montenegrin privatized companies covering the period 2004-7. Results show that ownership concentration and the presence of domestic and foreign private owners are positively related to firms' productivity. Companies that replaced the chairman of the management board also improved their productivity. The study further discusses the results in terms of the specific characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Additonally, they found that the firms with sufficient political power and intermediate levels of potential profitability will be the ones that choose to use stripped assets. There is further evidence of such outcomes (e.g., Gregurek, 2001, Gregoric, 2002, Cerovic and Mitrovic, 2007, Koman and Vasileva-Markovska, 2007, Koman et al, 2011. Koman et al (2015) tested econometric models of asset stripping in mass privatisation in Montenegro and found that, in the absence of the rule of law, many firms that appear to have disappeared in the process of privatisation were, in fact, expropriated by managers and individuals with political connections.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additonally, they found that the firms with sufficient political power and intermediate levels of potential profitability will be the ones that choose to use stripped assets. There is further evidence of such outcomes (e.g., Gregurek, 2001, Gregoric, 2002, Cerovic and Mitrovic, 2007, Koman and Vasileva-Markovska, 2007, Koman et al, 2011. Koman et al (2015) tested econometric models of asset stripping in mass privatisation in Montenegro and found that, in the absence of the rule of law, many firms that appear to have disappeared in the process of privatisation were, in fact, expropriated by managers and individuals with political connections.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Privatisation processes generally fall prey-as in the case of Serbiato asset stripping (see Hoff and Stiglitz, 2004). A number of works (Gregurek, 2001, Gregoric, 2002, Cerovic and Mitrovic, 2007, Koman and Vasileva-Markovska, 2007, Koman et al, 2011 highlight the negative role of asset stripping during privatisation. Campos and Giovannoni (2006) note that the propensity to strip assets is related to the power of the agent to influence the framework of privatisation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the more decentralized characteristic of the Yugoslav economy before privatization gave managers more information about their firm and its environment, which they used in the process of privatization. Anecdotal evidence as well as rather limited literature on this issue (e.g.,Gregurek (2001),Gregorič (2002),Cerović and Dragutinović Mitrović (2007),Koman and Hadži Vasileva -Markovska (2007),Koman et al (2011)) thus suggest that the model of management appropriation was common in the countries of former Yugoslavia, including Macedonia, BIH, Croatia and Serbia. The Slovenian situation was different in that the process of management buy-outs escalated only before the current crisis (see, for example,Prašnikar, Svejnar (2007),Domadenik et al (2008) andBole et al (2012)).…”
mentioning
confidence: 99%